Do quality indicators for general practice teaching practices predict good outcomes for students?. Issue 4 (3rd July 2016) - Bartlett, Maggie; Potts, Jessica; McKinley, Bob
Abstract: Keele medical students spend 113 days in general practices over our five-year programme. We collect practice data thought to indicate good quality teaching. We explored the relationships between these data and two outcomes for students; Objective Structured Clinical Examination (OSCE) scores and feedback regarding the placements. Though both are surrogate markers of good teaching, they are widely used. We collated practice and outcome data for one academic year. Two separate statistical analyses were carried out: (1) to determine how much of the variation seen in the OSCE scores was due to the effect of the practice and how much to the individual student. (2) to identify practice characteristics with a relationship to student feedback scores. (1) OSCE performance: 268 students in 90 practices: six quality indicators independently influenced the OSCE score, though without linear relationships and not to statistical significance. (2) Student satisfaction: 144 students in 69 practices: student feedback scores are not influenced by practice characteristics. The relationships between the quality indicators we collect for practices and outcomes for students are not clear. It may be that neither the quality indicators nor the outcome measures are reliable enough to inform decisions about practices' suitability for teaching.